Social entrepreneurs : mobilisers of social change - Crowther, David; Quoquab, Farzana (Developments in corporate governance and responsibility ;, 2022)
Social entrepreneurs greatly differ from other forms of entrepreneurs in terms of judgment capacity, pro-activeness, innovativeness, entrepreneurial virtue. They are often associated with social innovation and ascribed as transformational leaders due to their contribution in finding and initiating the positive change in solving any social problem. In recent years, the whole world is facing different aspects and levels of social problems. This has led to social entrepreneurs becoming more desired and attracting significant research attention. However, the discussion on such topic is still at its infancy with ongoing debates on its definition, characteristics, and roles. Social Entrepreneurs: Mobilisers of Social Change works to fill this gap in the literature, exploring the notion of social entrepreneurs, their role, facets, and implications to address the social problems. Developments in Corporate Governance and Responsibility offers the latest research on topical issues by international experts and has practical relevance to business managers. This is the only book series endorsed by the Social Responsibility Research Network.